Differences in nutritional status in pre-school children At the Muara Fajar-Riau Community Health Center - Singarimbun, Ristika Julianty (Sean Institute, 2022)
Nutritional status is a measure of success in fulfilling nutrition for pre-school children (aged 3-5 years) who come from the working area of ​​the Muara Fajar-Riau health center and is indicated by body weight and age or an indicator in measuring the nutritional status of the community because malnutrition can result in Various diseases such as calorie and protein deficiency, vitamin A, anemia, iron and iodine nutrition and the nutritional status of pre-school age can be divided into four, namely: over, good, under and poor nutritional status. Researchers aim to determine differences in nutritional status in pre-school children in the Muara Fajar-Riau health center working area. The sampling technique used in this research was Proportional Sample, the sample size obtained from each health center was: At the Muara Fajar-Riau Community Health Center there are 50 children aged 3-5 years. The total sample is 50 children aged 3-5 years in the Muara Fajar-Riau area using Total Sampling, the type of research is the analytical method using the independent t-test which obtained a p value = 0.000 (< 0.05), a significant hypothesis means there is Differences in nutritional status of pre-aged children between Muara Fajar-Riau Community Health Center working areas. It is hoped that the community health center can increase efforts to improve nutrition programs, increase families' awareness of the nutrition of pre-school age children, monitor mothers who do not want to visit the nearest health service with their children, and conduct outreach by providing information on nutritional developments to mothers who have Pre-school age children to avoid nutritional disorders.